Caracterização das argamassas históricas da Ruína de São Miguel Arcanjo/RS - Rodrigues, Paula Nader (2013)
Reduction of the Archangel Michael, is one of seven people missionaries who settled in Rio Grande do Sul, is dated approximately 1687 in the current site. Today the remains of their remaining part of National Heritage and Declared a World Heritage Site by UNESCO since 1983. The great importance of this historic site suggests research in studies on the mortar coating still exists in parts of the ruin. Discover the physical and chemical composition is one of the objectives of the research, which aims to identify the main constituents of the mortar materials, as well as whether or not the lime and the way it presents itself. In addition, to hypothesize the origin of the lime used or not of the Misiones region of RS. It also aims to demonstrate the importance of laboratory tests, such as X-Ray Diffraction, Thermogravimetric Analysis, Scanning Electron Microscopy (SEM), among others, in research and conservation of monuments. Through the XRD analysis and ATR-IR was verified using mortar nature calcite as well as the presence of aragonite in the second set (sacristy) and hydroxyapatite in the first set (front north). According to the history of the monument there is a probability of calcium carbonate is, the variation of aragonite, originated from the snail shell snail Physa SP. Kaolin analysis of this X-ray diffraction (XRD) analysis suggests a contamination of the substrate because the clay brick was spot. With the images obtained by SEM and EDS, showed the presence of organic fibers and a binder rich in calcium. The need for preventive conservation of monuments or buildings of historical interest makes this work of investigative and scientific nature. The knowledge of the original materials and the use of compatible materials for restoration is the first step to a good intervention and not to accelerate the deterioration of historic buildings.